Phonons and phase symmetries in bulk CrCl3 from scattering measurements and theory. (December 2022) - Li, Xun; Do, Seung-Hwan; Yan, Jiaqiang; McGuire, Michael A.; Granroth, Garrett E.; Mu, Sai; Berlijn, Tom; Cooper, Valentino R.; Christianson, Andrew D.; Lindsay, Lucas
Abstract: Phonon-derived behaviors are important indicators of novel phenomena in transition metal trihalides, including spin liquid behavior, two-dimensional magnetism, and spin-lattice coupling. However, phonons and their dependence on spin structure and excitations have not been adequately explored. In this work, we probe and critically examine the vibrational properties of the prototype ferromagnetic honeycomb lattice material CrCl3 using inelastic neutron scattering and density functional theory. We demonstrate that magnetic and van der Waals interactions are essential to describing the structure and phonons in CrCl3 ; however, the specific spin configuration is unimportant. This provides context for understanding thermal transport measurements as governed by dynamical spin-lattice couplings. More importantly, we introduce an efficient dynamic method that exploits translational symmetries in large conventional unit cells that generates insights into phonon dispersions, interactions, and measured spectra in terms of quantum phase interference conditions. This work opens new avenues for understanding phonons in layered magnets and more generally in conventional cell geometries of a variety of materials. Graphical abstract: Image, graphical abstract